Designed Natural Spaces: Informal Gardens Are Perceived to Be More Restorative than Formal Gardens - Twedt, Elyssa; Rainey, Reuben M.; Proffitt, Dennis R. (Frontiers in Psychology, 2016)
Experimental research shows that there are perceived and actual benefits to spending time in natural spaces compared to urban spaces such as reduced cognitive fatigue, improved mood, and reduced stress. Whereas past research has focused primarily on distinguishing between distinct categories of spaces (i.e., nature versus urban), less is known about variability in perceived restorative potential of environments within a particular category of outdoor spaces, such as gardens. Conceptually, gardens are often considered to be restorative spaces and to contain an abundance of natural elements, though there is great variability in how gardens are designed that might impact their restorative potential. One common practice for classifying gardens is along a spectrum ranging from “formal or geometric” to “informal or naturalistic”, which often corresponds to the degree to which built or natural elements are present, respectively. In the current study, we tested whether participants use design informality as a cue to predict perceived restorative potential of different gardens. Participants viewed a set of gardens and rated each on design informality, perceived restorative potential, naturalness, and visual appeal. Participants perceived informal gardens to have greater restorative potential than formal gardens. In addition, gardens that were more visually appealing and more natural-looking were perceived to have greater restorative potential than less visually appealing and less natural gardens. These perceptions and precedents are highly relevant for the design of gardens and other similar green spaces intended to provide relief from stress and to foster cognitive restoration.